The HER2 peptide nelipepimut-S (E75) vaccine (NeuVax™) in breast cancer patients at risk for recurrence: correlation of immunologic data with clinical response. (May 2014) - Schneble, Erika J; Berry, John S; Trappey, Francois A; Clifton, Guy T; Ponniah, Sathibalan; Mittendorf, Elizabeth; Peoples, George E
Nelipepimut-S (formerly known as E75) is an immunogenic peptide from the HER2 protein that is highly expressed in breast cancer. The NeuVax™ (Galena, OR, USA) vaccine, nelipepimut-S plus granulocyte–macrophage colony-stimulating factor, is designed for the prevention of clinical recurrences in high risk, disease-free breast cancer patients. Although cancer vaccines such as NeuVax represent promising approaches to cancer immunotherapy, much remains to be elucidated regarding their mechanisms of action: particularly given that multiple cancer vaccine trials have failed to demonstrate a correlation between immunologic data and clinical outcome. Here, we briefly discuss our clinical trial experience with NeuVax focusing on immunologic response data and its implication on how the immune system may be affected by this peptide vaccine. Most importantly, we demonstrate the potential capability of certain immunologic assays to predict clinical benefit in our trials.